Full-life growth behavior of a naturally initiated internal fatigue crack in beta titanium alloy via in situ synchrotron radiation multiscale tomography. (May 2023) - Xue, Gaoge; Nakamura, Takashi; Fujimura, Nao; Takahashi, Kosuke; Oguma, Hiroyuki; Takeuchi, Akihisa; Uesugi, Masayuki; Uesugi, Kentaro
Highlights: An internal fatigue crack in a beta titanium alloy was non-destructively monitored. The relation between fractographic features and crack growth stages was clarified. The formation of multiple facets was the dominant process of internal fracture. The crack blunting behaviors triggered crack growth from the facets to the matrix. The internal crack propagation rate was slower than that of the surface crack. Abstract: The full-life growth behaviors of an internal fatigue crack in a beta titanium alloy were non-destructively monitored using in situ synchrotron radiation multiscale computed tomography. The crack fronts at various cycles were superimposed on the fracture surface from the perspective of crack growth stages. The crack propagation process consisted of multiple facets formation and subsequent growth into the matrix and was dominated by the former process. The crack opening and blunting behaviors triggered crack growth from the facets to the surrounding matrix. The overall crack propagation rate of the internal crack was revealed to be slower than the surface crack.